Hippocampal projections to the anterior olfactory nucleus differentially convey spatiotemporal information during episodic odour memory - Afif J. Aqrabawi (Nature Portfolio, 2018)
Hippocampus is necessary for integrating the context with sensory cues to retrieve memory for unique episodes. Here, the authors show that inhibiting topographically organized projections from hippocampus to the anterior olfactory nucleus independently impairs spatial and temporal odour memory recall.